The Analysis Of Illocutionary Act in Hillary Clinton’s Speech - Lili Fitria Selfina Baok Baok; I Gusti Agung Sri Rwa Jayantini; I Dewa Ayu Devi Maharani Santika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
ABSTRACT This study deals with the types of illocutionary act in Hillary Clinton’s speech “American for Marriage Equality” at Human Right Campaign. This study aims to describe the types as well as the function of illocutionary act used in Hillary Clinton’s speech. The descriptive qualitative method was used to analyze the data in this study. The data are presented descriptively because it was described and explain illocutionary acts found in Hillary Clinton speech. The data were collected by found out the video and the script of the speech, watching the video and reading the script repeatedly then underline and quote the data which are related to the theory. The writer used Searle’s theory for the types of illocutionary acts which is divided into 5 types namely assertive, directive, commisive, expressive, and declaration. And used the theory proposed by Leech’s for the function of illocutionary acts which is divided into 4 categories they are competitive, convivial, collaborative, conflictive. The writer formulated research questions are: 1.What are the types of illocutionary act found in Hillary Clinton’s speech “American for Marriage Equality” at Human Right Campaign? 2. What are the functions of illocutionary acts used in Hillary Clinton’s speech” at Human Right Campaign?. Data source of this study were taken from Hillary Clinton’s speech text “American for Marriage Equality” at Human Right Campaign. Generally, the result of this study shows that this speech text is analyzed in four types of illocutionary act: assertive 5 data (45,45%), directive 3 data (27,27%), commisive 1 data 9,10%), and expressive 2 data (18,18%). And the function of illocutionary act the writer found convivial 3 data (75%) and collaborative 1 data (25%). Key words: speech act, illocutionary acts, speech Abstrak Penelitian ini membahas tentang macam-macam tindak ilokusi dan fungsi tindak ilokusi dalam pidato Hillary Clinton “American for Marriage Equality” at Human Right Campaign. Masalah penelitian ada dua yaitu 1. Apa saja jenis tindak ilokusi yang terdapat dalam pidato Hillary Clinton? 2. Apa saja fungsi dari tindak ilokusi yang digunakan dalam pidato Hillary Clinton? Adapun metode yang digunakan dalam penelitian adalah metode kualitatif. Data dikumpulkan dengan cara mencari video dan naskah pidato, menonton video dan membaca naskah berulang kali, menggaris bawahi dan mengutip data yang berhubungan dengan teori. Secara umum, hasil penelitian ini menunjukan bahwa teks pidato ini dianalisis dalam empat jenis tindak ilokusi yaitu assertive 5 data (45,45%), directive 3 data (27,27%), commisive 1 data 9,10%), and expressive 2 data (18,18%). Dan fungsi dari tindak ilokusi penulis menemukan convivial 3 data (75%) and collaborative 1 data (25%). Kata kunci : tindak tutur, tindak ilokusi, pidato